Understanding Entrepreneurship: A Wealth of Opportunities (International Journal of Scientific Research and Management (IJSRM), 2016)
Entrepreneurship is perceived as vital instrument for sustainment of any economy and its international progress. Moreover, recognizing and choosing appropriate opportunities for new ventures is one of the most significant skills of an accomplished entrepreneur. On the other hand, entrepreneurs recognize opportunities for creating and delivering value stakeholders in the future businesses. Whereas, components of an opportunity might be identified, opportunity are created and not discovered. This research presents an existing platform of entrepreneurial opportunity recognition and its development and employs Dubin’s (1978) theory building framework. The research critically reviewed various theories proposed by several authors in order to gain superior knowledge of entrepreneurial opportunities. The research is based on secondary data sources. Moreover, this research has employs Dubin’s (1978) theory building framework in order to recognize entrepreneurial opportunities and their development. Finally, conclusion was made and area for further research has been suggested in order to support the feasibility of the subject.